2021
DOI: 10.3390/app11020640
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Dental Implants Placed in Low-Quality Bone Sites Prepared for the Healing Chamber with Osseodensification Concept: A Double-Blind, Randomized Clinical Trial

Abstract: The present study aimed to compare the stability of dental implants placed in low-quality bone prepared for the healing chamber with osseodensification technique and a standard undersized drilling. Sixteen subjects presenting D3 or D4 bone density according to Misch’s classification were randomly distributed to receive dental implants following either osseodensification (G1: n = 29) or standard undersized drilling (G2: n = 26) preparation techniques. Implant insertion torque (IT) and implant stability quotient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…The neovascularization was evaluated using the scores system from ISO 10993-6/2016: no capillary proliferation (0); minimal capillary proliferation, focal 1-3 buds (1); groups of 4-7 capillaries with supporting fibroblastic structure (2); broad band of capillaries with supporting structures (3); extensive band of capillaries with supporting fibroblastic structures (4). The values are presented as median ± confidence interval (n = 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neovascularization was evaluated using the scores system from ISO 10993-6/2016: no capillary proliferation (0); minimal capillary proliferation, focal 1-3 buds (1); groups of 4-7 capillaries with supporting fibroblastic structure (2); broad band of capillaries with supporting structures (3); extensive band of capillaries with supporting fibroblastic structures (4). The values are presented as median ± confidence interval (n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…All previous animal studies aimed to investigate the bone-implant contact and bone area fraction occupancy at different time points and macro/micro geometries. Furthermore, two clinical trials 4,39 aimed to compare the insertion torque and implant stability of implants placed via OD and SCD. The present study evaluated for the first-time histological events around nanohydroxyapatite dental implant coating using different drilling techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the current study was a randomized controlled study that included a single implant system with regular implant diameter and length and D3-D4 bone mineral density, this may explain the different results obtained in this study. Also, Mello-Machado et al [21], in a randomized clinical study, compared OD drilling with standard undersized drilling in D3-D4 bone, and They concluded that OD enabled the concept of a bone healing chamber in low-quality bone without affecting implant stability or success rates.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized clinical trial [33] comparing OD instrumentation and undersized drilling protocol, the authors achieved 100% survival rates for both groups. Interestingly, the results showed that, even with a wider implant site preparation, the OD group reached installation torques higher than the undersized drilling group.…”
Section: Introductionmentioning
confidence: 99%